Some biblical Hebrew influence on the Karaim bible translations: The Book of Leviticus, Gözleve Bible (1841) - Işık, Murat (Études sur la Région Méditerranéenne, 2020)
The Karaims are a Turkic community living in Eastern Europe who are the followers of Karaism/Karaite Judaism. Their faith acknowledges the Tanakh as the sole source whereas it does not recognize the Talmud which is the written collection of the oral tradition. Thence, starting from the early periods, the Hebrew Bible has long been translated into the Karaim language. Such translations are important to demonstrate the features of the highly endangered Karaim language that belongs to the Kipchak (North-Western) group of the Turkic languages. Thus, after a long hiatus, scholars have developed a renewed interest in Karaim Bible translations as well. However, these translations show some common Hebrew characteristics that mainly appear on morphological and syntactic structures whereas they usually do not occur in the spoken language. In this regard, the present study is going to present such Hebrew influences that occur in the Book of Leviticus of the so-called Gözleve Bible (1841) which was published in Crimea in an extinct Eastern variety of Karaim Language (Crimean Karaim).